Flexible strain sensors based on electrostatically actuated graphene flakes. (8th June 2015) - Fardindoost, Somayeh; Alipour, Akbar; Mohammadi, Saeed; Gokyar, Sayim; Sarvari, Reza; Iraji zad, Azam; Demir, Hilmi Volkan
Abstract: In this paper we present flexible strain sensors made of graphene flakes fabricated, characterized, and analyzed for the electrical actuation and readout of their mechanical vibratory response in strain-sensing applications. For a typical suspended graphene membrane fabricated with an approximate length of 10 µ m, a mechanical resonance frequency around 136 MHz with a quality factor ( Q ) of 60 in air under ambient conditions was observed. The applied strain can shift the resonance frequency substantially, which is found to be related to the alteration of physical dimension and the built-in strain in the graphene flake. Strain sensing was performed using both planar and nonplanar surfaces (bending with different radii of curvature) as well as by stretching with different elongations.